2009
DOI: 10.1002/cii.357
|View full text |Cite
|
Sign up to set email alerts
|

The transmeatal approach: a new technique in cochlear and middle ear implants

Abstract: The transmeatal approach (TMA) is a new approach for cochlear and middle-ear implantation. It is an open-tunnel technique that differs from closed transcanal non-mastoidectomy approaches. The TMA involves creating an open transcanal tunnel starting from the annulus superior to the chorda tympani laterally towards the suprameatal region. Then, through the open tunnel, a bony groove is created in the bone underneath the length of the external auditory canal (EAC) to protect the electrode from extrusion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…A follow-up after surgery, we confirmed that patency of the EAC was maintained and the electrodes' function was normal. A study including 131 patients who underwent CI using the transmeatal approach with followup of 2 to 46 months reported no electrode extrusion in the cartilage area [8]. A study with long-term follow-up is necessary to confirm favorable outcomes at the cartilage site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A follow-up after surgery, we confirmed that patency of the EAC was maintained and the electrodes' function was normal. A study including 131 patients who underwent CI using the transmeatal approach with followup of 2 to 46 months reported no electrode extrusion in the cartilage area [8]. A study with long-term follow-up is necessary to confirm favorable outcomes at the cartilage site.…”
Section: Discussionmentioning
confidence: 99%
“…In conventional CI, canal wall-up mastoidectomy and posterior tympanotomy have been used; in addition, a transmeatal approach to insert the electrode array through the external auditory canal (EAC) has been proposed [8]. This technique involves bypass of the mastoid cavity, which can improve the suprameatal approach [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transmeatal approach provides an excellent view to the round window and involves drilling a tunnel visibly in the external canal [10]. However, electrode extrusion, external infection with persistent otorrhea, and cholesteatoma are complications that may arise from the transmeatal approach.…”
Section: Discussionmentioning
confidence: 99%
“…Taibah K, reported 5 cases out of 134 case of tympanic membrane perforation that was healed spontaneously with conservative measures (9).…”
Section: -Tympanic Membrane Affectionmentioning
confidence: 99%